Răspuns :
E (x ) = ( x + 2)² · x / x·( x +2) ·( x +2)
E ( x ) = ( x + 2)² · x / x · ( x +2)²
E(x) = 1
E ( x ) = ( x + 2)² · x / x · ( x +2)²
E(x) = 1
(x²+4x+4)/[x*x/x+2/x*(x+2)]=(x²+4x+4)/[x*(x+2)/x*(x+2)]=
=[(x+2)(x+2)]/[x*(x+2)/x*(x+2)]=(x+2)²/[x*(x+2)/x*(x+2)]=
=[x(x+2)²]/[x*(x+2)(x+2)]=(x+2)²/[(x+2)(x+2)]=(x+2)²(x+2)⁻²=
=(x+2)²⁻²=(x+2)⁰=>
=>(x+2)⁰=1 raspunsul deci este 1
{x∈R:x≠-2 si x≠0}
E(x)=1
=[(x+2)(x+2)]/[x*(x+2)/x*(x+2)]=(x+2)²/[x*(x+2)/x*(x+2)]=
=[x(x+2)²]/[x*(x+2)(x+2)]=(x+2)²/[(x+2)(x+2)]=(x+2)²(x+2)⁻²=
=(x+2)²⁻²=(x+2)⁰=>
=>(x+2)⁰=1 raspunsul deci este 1
{x∈R:x≠-2 si x≠0}
E(x)=1